Menggali Kreativitas dalam Pembelajaran IPS Melalui Pedagogi Kreatif - Nanang Kosim; Nana Supriatna (Yayasan Perguruan Kampus, 2024)
Education in social studies is no longer just about transferring facts, but also about shaping critical and creative thinking. In this context, the creative pedagogy approach emerges as an interesting method to enrich social studies learning. This article aims to explore the concept of creative pedagogy in social studies learning and explore its potential to improve student understanding. Through a literature review and analysis of current research, we explain the concept of creativity in an educational context and review the relevance of creative pedagogy in the context of social studies learning. The research methodology used includes a literature search as well as an analysis of findings from relevant empirical research. The findings show that the use of creative pedagogy can contribute positively to social studies learning by strengthening students' understanding, stimulating interest in learning and developing critical skills. However, challenges in implementing this approach were also identified. A discussion on the implications of the findings of this study in the context of social studies learning practice is presented, as well as suggestions for further research. In conclusion, the creative pedagogy approach promises to take social studies learning to a higher level by strengthening students' creativity and preparing them to face future global challenges.